2003
DOI: 10.1007/s00125-003-1079-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of a novel mutation of hepatocyte nuclear factor-1α gene in a Korean family with MODY3

Abstract: Aims/hypothesis. After screening 16 Korean families with early onset Type 2 diabetes in search for hepatocyte nuclear factor (HNF)-1α gene mutation, we identified a novel missense mutation (R263L) associated with MODY phenotype. We studied the biological characteristics of the mutation and the potential functional consequences based on the crystallographic structure of HNF-1α in complex with DNA. Methods. DNA from subjects with a familial form of early onset diabetes was isolated and HNF-1α was sequenced. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…It has been reported that the R295H mutant exhibited target-specific effects of activation in which the transactivation potential of R295H on the HNF4α promoter reached to wild-type transactivation level, while transactivation of either Afp or albumin promoter by this mutant were barely detectable (49). In other studies, the corresponding mutants R263C/L in HNF1α showed greatly reduced DNA binding activity as a result of these more drastic substitutions (52,53).…”
Section: Disease-related Mutationsmentioning
confidence: 90%
“…It has been reported that the R295H mutant exhibited target-specific effects of activation in which the transactivation potential of R295H on the HNF4α promoter reached to wild-type transactivation level, while transactivation of either Afp or albumin promoter by this mutant were barely detectable (49). In other studies, the corresponding mutants R263C/L in HNF1α showed greatly reduced DNA binding activity as a result of these more drastic substitutions (52,53).…”
Section: Disease-related Mutationsmentioning
confidence: 90%
“…Among the 69 patients, only 10 patients had autosomal dominant inheritance of type 2 DM in at least three generations. Kim et al [16]. reported that one patient (6.3%) with an HNF-1a R267L mutation was detected among 16 unrelated patients diagnosed with type 2 DM before the age of 35 years who had autosomal dominant inheritance of type 2 DM in at least two generations.…”
Section: Discussionmentioning
confidence: 99%
“…The chromatin remodeling involves recruitment of HATs (e.g., p300/CBP), resulting in hyperacetylation of histones at specific promoters, including GLUT2 and pyruvate kinase, in β-cells (8688). Interestingly, a missense mutation (R263L) in the HNF1A gene that is associated with a MODY phenotype results in reduced affinity for p300 (89). Moreover, MODY mutations in the HNF1B gene influence the capacity of HNF1β to bind proteins with HAT activity and may thereby affect the chromatin structure (90).…”
Section: Monogenic Diabetes and Epigenetic Factorsmentioning
confidence: 99%